TRANSFORMING THE MINANGKABAU CATUR HARIMAU GAME INTO A CONTEMPORARY ILLUSTRATIVE MURAL - Bayu Rahmad Trisya; Riswel Zam (Journal of Social Science, 2026)
Objective: Catur Harimau is a Minangkabau traditional strategy game involving three tiger pieces and twenty-two goat pieces. In the observed communities, direct play practices and intergenerational transmission have become increasingly difficult to encounter. This article explains how the game's structure, strategic values, and cultural identity were transformed into a contemporary illustrative mural. Method: The creation employed practice-based research through artistic inquiry, material mapping, visual and technical exploration, design, realization, and reflection. Data were gathered through literature review, observation of the game and site, visual documentation, virtual exploration, and interviews with four informants in Agam and Bukittinggi. Results: The outcome is Catur Harimau Reborn, a 10 × 2.5 metre mural at Sekolah Alam Bukittinggi. The game board forms the compositional centre, while a tiger, a goat, seven children, Rumah Gadang, mountains, marawa colours, and typography construct an accessible cultural narrative. Novelty: Its novelty lies in translating a traditional game into public art, developing simple counters into expressive anthropomorphic characters, and inviting viewers to engage through visual reading. The mural offers a visual framework for cultural communication and education; however, its actual audience impact requires a separate reception study.